The Nehari Manifold and Application to a Quasilinear Elliptic Equation with Multiple Hardy-type Terms (Journal of Partial Differential Equations, 2013)
In this paper, by using the Nehari manifold and variational methods, we study the existence and multiplicity of positive solutions for a multi-singular quasilinear elliptic problem with critical growth terms in bounded domains. We prove that the equation has at least two positive solutions when the parameters λ belongs to a certain subset of R.